Preserving the Person A Look At The Human Sciences - Evans, C. Stephen (Vancouver Regent College Publishing, 1994)
The human quest for self-understanding is ancient. It transcends the boundaries between ordinary folk and philosophers and it overlaps with many academic disciplines, including psychology, sociology, philosophy and theology. Actually, the quest is not
Keywords: Personalism. Philosophical anthropology